2010
DOI: 10.1093/cercor/bhp317
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Regulation of Striatal Medium Spiny Neuron Dendritic Remodeling in Parkinsonism: Modulation of Glutamate Release Reverses Dopamine Depletion–Induced Dendritic Spine Loss

Abstract: Striatal medium spiny neurons (MSNs) receive glutamatergic afferents from the cerebral cortex and dopaminergic inputs from the substantia nigra (SN). Striatal dopamine loss decreases the number of MSN dendritic spines. This loss of spines has been suggested to reflect the removal of tonic dopamine inhibitory control over corticostriatal glutamatergic drive, with increased glutamate release culminating in MSN spine loss. We tested this hypothesis in two ways. We first determined in vivo if decortication reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 76 publications
1
68
0
Order By: Relevance
“…This finding is consistent with the previously observed intrinsic connectivity between the putamen and parietal cortex (Martino et al, 2008; Cao et al, 2009). To this end, given that the putamen consists primarily of spiny neurons which receive direct input from glutamatergic signaling, tDCS may also influence the inhibitory medium spiny neurons in this brain structure (Garcia et al, 2010; Girault, 2012). However, the putamen and the cortex have no monosynaptic anatomical connections, and so further research is needed to identify the mediating structures and signaling pathways by which tDCS operates.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the previously observed intrinsic connectivity between the putamen and parietal cortex (Martino et al, 2008; Cao et al, 2009). To this end, given that the putamen consists primarily of spiny neurons which receive direct input from glutamatergic signaling, tDCS may also influence the inhibitory medium spiny neurons in this brain structure (Garcia et al, 2010; Girault, 2012). However, the putamen and the cortex have no monosynaptic anatomical connections, and so further research is needed to identify the mediating structures and signaling pathways by which tDCS operates.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that glutamatergic synaptic and intraspine calcium channel dysregulation may play key roles in PD-related striatal spine pathology (Villalba and Smith, 2010; Burguière et al, 2013; Tian et al, 2010). Previous studies have shown that reducing glutamate release may prevent and/or reverse dopamine depletion-induced dendritic spine loss on medium spiny neurons (Neely et al, 2007; Garcia et al, 2010). In addition, the administration of an L-type calcium channel blocker in an animal model was shown to attenuate these spine losses (Soderstrom et al, 2010; Schuster et al, 2009; Bezard, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Corticostriatal synapses have been shown to be overactive in dopamine-depleted animals (Picconi, Centonze et al 2004, Centonze, Gubellini et al 2005), contributing to the loss of spines in striatal medium spiny neurons in PD (Garcia, Neely et al 2010). In addition, the deregulated plasticity (such as long-term depression and depotentiation) at corticostriatal synapses may underlie the mechanism of L-DOPA-induced dyskinesias (Picconi, Centonze et al 2003, Picconi, Bagetta et al 2011).…”
Section: Therapeutic Indications Of Mglusmentioning
confidence: 99%